PARENTS' CONCEPT OF EDUCATION FOR CHILDREN IN STRENGTHENING RELIGIOUS BASIS - Latifiudin Al-islamy; Eneng Muslihah; Machdum Bahtiar; Wasehudin; Rifyal A. Lughowi (Fakultas Tarbiyah IAI Darussalam, 2025)
Parents have a good role for their children in educating them, especially educating them in the teachings of good Islamic education. Basically, the first and foremost educational environment for children is education that comes from the family environment. One of the Islamic education that must be had and instilled from an early age is prayer. Prayer is a type of education that is instilled from an early age and is required to be done after reaching puberty. In various aspects, prayer itself has various aspects in education, such as education for children, education for parents and education for the people of the Prophet Muhammad SAW. This research refers to the case study of Q.S Lukman Verse: 17, using the Library Research method. In order to know how prayer can be used as a solid foundation for Islamic religious education. This concept will be an improvement for the development of the basics of Islamic education in children.